Analisis Kompetensi Sosial Guru terhadap Pembentukan Karakter Siswa di SD/MI: Kajian Literatur Kualitatif - Hofsawati Nengseh; Imron Fauzi (Mathematics Education Study Program, 2025)
Character education is a fundamental aspect of shaping students’ personality and morality from an early age. In this context, teachers’ social competence plays a crucial role, as it directly influences their ability to create meaningful and value-based educational interactions. This study aims to describe the role of teachers’ social competence in shaping students’ character at elementary schools and Islamic elementary schools (SD/MI). The research employs a qualitative method with a library research approach, analyzing 35 scientific sources published between 2020 and 2025, including accredited national journals, reference books, and relevant research reports. The findings indicate that teachers’ social competence, particularly communication skills, empathy, cooperation, and exemplary behavior has a significant impact on the development of students’ character, especially in the aspects of responsibility, discipline, and honesty. Teachers with strong social competence are able to create a positive learning environment, internalize moral values, and serve as role models for their students. The implication of this study emphasizes the importance of strengthening teachers’ social competence through professional development and training programs to support the effective and sustainable implementation of character education in elementary and Islamic elementary schools.